H2S and SO2 adsorption on Cu doped MoSe2: DFT investigation - Ahmad I. Ayesh (10188469) (2022)
Hydrogen sulfide and sulfur dioxide are highly hazardous gases, thus, the development of highly sensitive and selective materials for their adsorption is desirable. The effect of Cu doping of MoSe2 on its adsorption for both H2S and SO2 gases is investigated in this work using first principles density functional theory (DFT) computations. The band gap, adsorption distance, adsorption energy, density of states, and charge transfer are examined in details. The results illustrate significant changes of the electronic properties as well as adsorption for H2S and SO2 gases of MoSe2 due to doping with Cu. The results reveal significant changes in the density of states and band gap upon doping with Cu that enhance the adsorption of both H2S and SO2 gases on MoSe2 system. Nevertheless, the Cu-modified MoSe2 system exhibits higher adsorption energy towards H2S thus higher sensitivity as compared with SO2. The results demonstrate that the Cu-modified MoSe2 system can be applied successfully for H2S gas sensor applications. Other Information Published in: Physics Letters A License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.physleta.2021.127798